โครงการจัดทำแผนชุมชนที่สอดคล้องกับวิถีชีวิตแบบมีส่วนร่วมของคนในหมู่บ้านโคกแฝก ตำบลขามทะเลสอ อำเภอขามทะเลสอ จังหวัดนครราชสีมา - เลิศยิ่งยศ, ศิริพร (Naresuan University Journal: Science and Technology (NUJST); Vol 21 No 1 (2013): January-March 2013, 2014)
การวิจัยครั้งนี้เปิดโอกาสให้คนในชุมชนเข้ามามีส่วนร่วมในการคิดวิเคราะห์สภาพปัญหาและความต้องการที่แท้จริงของคนในชุมชน โดยตระหนักถึงวิถีชีวิตและศักยภาพที่มีอยู่ในชุมชนเพื่อนำมาวางแผนงานของชุมชนบนพื้นฐานของทุนชุมชน ซึ่งมีวัตถุประสงค์เพื่อ 1) ศึกษาวิถีชีวิตและศักยภาพของคนในชุมชนหมู่บ้านโคกแฝก ตำบลขามทะเลสอ อำเภอขามทะเลสอ จังหวัดนครราชสีมา 2) เพื่อจัดทำแผนชุมชน ที่สอดคล้องกับวิถีชีวิตด้วยการมีส่วนร่วมของคนในหมู่บ้านโคกแฝก ตำบลขามทะเลสอ อำเภอขามทะเลสอ จังหวัดนครราชสีมา กลุ่มตัวอย่าง ได้แก่ กลุ่มผู้นำและกรรมการหมู่บ้านโคกแฝก กลุ่มผู้ประกอบอาชีพเกษตรกร กลุ่มผู้ประกอบอาชีพรับจ้าง/ลูกจ้างและกลุ่ม ผู้ประกอบอาชีพค้าขาย โดยมุ่งเน้นให้ประชาชนมีส่วนร่วมจัดทำแผนชุมชนทุกขั้นตอนและนำมาสร้างข้อสรุปโดยใช้การบรรยายเชิงพรรณา (Descriptive Analysis)       ผลการวิจัย พบว่า ส่วนใหญ่คนในชุมชนหมู่บ้านโคกแฝกอยู่ร่วมกันแบบเครือญาติ ลักษณะครอบครัวขยาย มีความเอื้อเฟื้อเผื่อแผ่กันตลอดเวลา มีการถ่ายทอดวิถีชีวิตความเป็นอยู่ ความเชื่อต่างๆ มาสู่ลูกหลาน โดยมีศาสนาเป็นเครื่องยึดเหนี่ยวจิตใจ ข้อมูลทางด้านศักยภาพของชุมชน พบว่า ชุมชนมีศักยภาพหลายด้านที่สามารถนำมาใช้ประกอบในการจัดทำแผนชุมชนที่สอดคล้องกับวิถีชีวิตของคนในหมู่บ้านโคกแฝก เช่น ด้านทรัพยากรธรรมชาติ มีสภาพดินดีไม่เค็ม ส่งผลให้ทำการเกษตรได้ผลดีด้านการศึกษา มีโรงเรียนบ้านโคกแฝก ซึ่งเป็นสถานศึกษาขั้นพื้นฐานให้ สังคมมีส่วนร่วมในการจัดการศึกษาและการพัฒนาสาระและกระบวนการเรียนรู้อย่างต่อเนื่อง ด้านการประกอบอาชีพของคนในชุมชนหมู่บ้านโคกแฝก แบ่งตามวิถีชีวิตได้3 กลุ่ม คือ 1) ผู้ประกอบอาชีพเกษตรกรมีความเชี่ยวชาญตั้งแต่บรรพบุรุษและสามารถถ่ายทอดให้กับคนรุ่นใหม่ได้ไม่ว่าจะเป็น การทำฟาร์มโคนม โคเนื้อ การปลูกผัก เป็นต้น 2) กลุ่มผู้ประกอบอาชีพรับจ้าง/ลูกจ้าง ส่วนใหญ่เป็นคนรุ่นใหม่ มีความพร้อมรวมกลุ่มอาชีพ เพื่อเสริมสร้างผลิตภัณฑ์ในหมู่บ้าน เช่น พัฒนาผลิตภัณฑ์ครีมบำรุงผิว ตัดเย็บผ้า เป็นต้น 3) กลุ่มผู้ประกอบอาชีพค้าขายในชุมชน มีศักยภาพที่ จะได้รับการส่งเสริมให้แปรรูปผลิตภัณฑ์ในชุมชนเพื่อการจัดจำหน่าย เช่น ปลูกผักปลอดสารพิษ การทำไข่เค็มดินปลวก เป็นต้น จากการศึกษาวิถีชีวิต และศักยภาพของชุมชนหมู่บ้านโคกแฝกทำให้เห็นถึงโอกาสที่ชุมชนจะได้รับการพัฒนา ผู้วิจัยได้ใช้กระบวนการวิจัยแบบมีส่วนร่วม (Participatory Action Research : PAR) จัดทำแผนชุมชนที่สอดคล้องกับวิถีชีวิตของคนในชุมชนหมู่บ้านโคกแฝก โดยเน้นการมีส่วนร่วมทุกขั้นตอนตั้งแต่การศึกษา บริบทชุมชน จัดเวทีประชาคมเพื่อชี้แจง สร้างความเข้าใจกับประชาชนในการจัดทำแผนชุมชน การสนทนากลุ่มเพื่อวิเคราะห์ศักยภาพชุมชน จัดเวทีวิเคราะห์สภาพปัญหาและหาแนวทางแก้ไข โดยร่วมกันกำหนดแผนงาน โครงการ กิจกรรมพัฒนาชุมชนตามวิถีชีวิตของแต่ละกลุ่มอาชีพ และเปิดโอกาสให้ประชาชนมีส่วนร่วมคัดเลือกโครงการและวัดผลสำเร็จโครงการ จากกระบวนการมีส่วนร่วมครั้งนี้ ส่งผลให้เกิดแผนชุมชน ที่สอดคล้องกับวิถีชีวิตของคนในชุมชนหมู่บ้านโคกแฝกจำนวน 3 แผนงาน ได้แก่แผนชุมชนที่สอดคล้องกับวิถีชีวิตของคนในกลุ่มอาชีพเกษตรกร แผนชุมชนที่สอดคล้องกับวิถีชีวิตของคนในกลุ่มอาชีพรับจ้าง/ลูกจ้าง และแผนชุมชนที่สอดคล้องกับวิถีชีวิตของคนในกลุ่มอาชีพค้าขาย โดยแผนที่ได้มีความแตกต่างจากแผนที่หน่วยงานภาคราชการจัดทำขึ้น เพราะส่วนใหญ่เป็นแผนที่ถูกกำหนดเพื่อประกอบการจัดสรร งบประมาณเท่านั้น การจัดทำแผนชุมชนครั้งนี้ คณะผู้วิจัยได้ยึดวิถีชีวิตและศักยภาพที่มีอยู่ในชุมชนเป็นหลัก ซึ่งได้แก่ เงินทุน ทรัพยากร ภูมิปัญญา วัฒนธรรม สิ่งแวดล้อม โดยเน้นการมีส่วนร่วมของประชาชนเข้ามาร่วมกันคิด การแสดงความคิดเห็น การแลกเปลี่ยนเรียนรู้ เพื่อหาแนวทาง/กิจกรรมการพัฒนาและแก้ไขปัญหาชุมชนด้วยตนเอง มีการตัดสินใจร่วมกับประชาชนอย่างจริงจัง รวมถึงสร้างการเรียนรู้ร่วมกัน และความรู้สึกเป็นเจ้าของร่วมกัน ซึ่งจะส่งผลให้ประชาชนหมู่บ้านโคกแฝกเล็งเห็นความสำคัญและสมัครใจที่จะเข้ามามีส่วนร่วมในการจัดทำ แผนชุมชนที่สอดคล้องกับวิถีชีวิตของคนในหมู่บ้านโคกแฝก อันเป็นแนวทางขับเคลื่อนและเกิดการพัฒนาหมู่บ้านได้อย่างเข้มแข็ง และยั่งยืนต่อไป          This research give to opportunities for people participation. They analysis problems and needs of the community. They recognizing the life and potential that exists in the community on the basic of community plan. the objectives of this research were 1) to study the potential of community life and people in the Khok Fhak village, Kham Thale So, Nakhon Ratchasima, 2) to create the community plans that corresponds to the living by the cooperation of people in the Khok Fhak village, Tumbon Kham Thale So, Amphur Kham Thale So, Nakhon Ratchasima. The samples of this research were Khok Fhak village leaders, board of directors, agriculture group, labor group, and merchandise group. The research focused on the cooperation of the community in every process to create the plans that correspond to their living. Then, the results were explained by using descriptive analysis.       The results found that the majority of Khok Fhak’s lifestyle is extended family (living together and supporting each other). They pass down their way of life and religion’s belief to their lineage. The potential community data were found that this community has many potential to be supported in forming community plans which related to Khok Fhak’s living. For instance, their good natural source is advantage in agriculture. Second, their education, Ban Khok Fhak School is a fundamental in encouraging their community to participate in educational management and learning process development continually. Third, their occupation can be divided by their living into 3 groups as follows; 1) Agricultural group, their ancestors are expertise in this field for ages and they carried on their skills to next generation such as dairy farming, cattle farming, vegetable planting etc. 2) Labor group, most of them are new generation which are grouped to produce their local products such as skin cream products, sewing etc. 3) Merchandise group, they will transform their local products for selling such as organic planting, termite‐soilsalted‐ egg making, and etc. From the study of the lifestyle and the potential community of Khok Fhak village, this is a good opportunity of its community to be developed. Therefore, the researchers decided to use Participatory Action Research (PAR) to forming community plans which related to their living. This plan emphasis on the participation of Khom Fhak people which are; studying the context of the community, making the community understand about the plan, providing the community forum to clarify the issues and to analyze the potential community and the problems, finding the solutions including the participation of planning and developing the activities of the community in each occupation. This participation leads to establish three community plans that correspond to the lifestyle of agricultural group, labor group and merchandise group in the Khok Fhak village. These plans are different from the prior plans of the state agencies which determined by the Government to allocate its budget only. In this community plans, the researchers considered on the lifestyle and the potential of community which are the capital, the resources, the wisdom, the culture, and the environments. It’s emphasized on the participation of the community to find the way to develop activities and solve their own problems. In addition, they had a chance to share their opinion and learning, to agree with the suggestions and the decisions, and to generate a collaborative learning and share the sense of ownership. These mentions can encourage the Khok Fhak people to realize the importance of the plans, and to participate willingly in the preparation of community plans which correspond to their lifestyle. This can be a principle to develop their living more strongly and sustainably.
Keywords: แผนชุมชนชุมชน; การมีส่วนร่วมของประชาชน; plan in line with community life, participation of villagers